Cooperative security to face the subregional conflict - Jarrín, Oswaldo (2016)
This article analyzes the impact of the Colombian conflict on the security of the Andean region, taking as a focal point its impact on Ecuador. The author highlights the social vulnerabilities of the Ecuadorian northern border, and considers that a regional framework of cooperation as an option for confronting current regional threats. Finally, the author makes a case for a cooperative security perspective aimed at approaching regional conflicts in all their complexity.